The concept of Yi (义) in the Mencius and the problems of distributive justice - TAN, Sor-hoon (Institutional Knowledge at Singapore Management University, 2014)
This paper examines attempts to find a conception of justice in early Confucian contexts, focusing on the concept of yi (translated as ‘appropriateness’, ‘right’, ‘rightness’, even ‘justice’) in the Mencius. It argues against the approach of deriving principles of dividing burdens and benefits from the discussions of concrete cases employing the concept of yi and instead shows that Confucian ethical concerns are more attentive to what kinds of interpersonal relations are appropriate in specific circumstances. It questions the exclusive emphasis in justice-centred ethical discourse on assessing actions, and even more narrowly actions of governments and other public institutions, and their consequences regarding distribution of rights and material resources and goods. Instead of applying some abstract principles of justice, whether of equality or some other priorities according to individual characteristics, distributive problems are approached from the perspective of the effect of any proposed distribution on interpersonal relationships. Principles of justice treat opportunities, resources, and goods that are supposed to be distributed as possessions or potential possessions of individuals always competing for resources and goods. Confucians treat them not as objects to be possessed by one and denied to others, but as facilitators of personal cultivation effecting appropriate interpersonal relationships constituting harmonious communities. The Mencius offers a different perspective on distributive problems by shifting our ethical attention from ‘who gets what?’ to ‘how should we relate to others?’ within a different conception of the good life and the ideal society or polity.